Achieving high out-of-plane thermal conductivity for boron nitride nano sheets/epoxy composite films by magnetic orientation. (June 2022) - He, Yifan; Kuang, Fengxia; Che, Zhanxun; Sun, Fangyuan; Zheng, Kun; Zhang, Jingnan; Cao, Xinyu; Ma, Yongmei
Abstract: The preparation of boron nitride nanosheet (BNNS)/polymer composite films with high out-of-plane thermal conductivity ( K ) remains a challenge. Here, we obtained BNNS/epoxy (EP) resin composite films with well aligned BNNSs exhibiting a high K in the out-of-plane direction through the careful optimization of the magnetic field strength. Firstly, magnetically responsive BNNSs (m-BNNSs) with a large surface area were prepared by loading Fe3 O4 nanoparticles via in situ co-precipitation. Secondly, m-BNNSs were incorporated into EP to prepare well aligned m-BNNS/EP composites by controlling the intensity and direction of the magnetic field. The results show that the BNNSs are well oriented in the out-of-plane direction, resulting in a K as high as 14.55 Wm −1 K −1 for 30.0- wt% BNNS loading, which is 4.5 times higher than that of unoriented films and 70 times higher than that of pure EP. This strategy can be extrapolated to obtain polymer composite films filled with other two-dimensional materials.